Phylogeny and abiotic conditions shape the diel floral emission patterns of desert Brassicaceae species. (25th April 2021) - Cna'ani, Alon; Dener, Efrat; Ben‐Zeev, Efrat; Günther, Jan; Köllner, Tobias G.; Tzin, Vered; Seifan, Merav
Abstract: A key facet of floral scent is diel fluctuations in emission, often studied in the context of plant‐pollinator interactions, while contributions of environment and phylogeny remain overlooked. Here, we ask if these factors are involved in shaping temporal variations in scent emission. To that end, we coupled light/dark floral emission measurements of 17 desert Brassicaceae species with environmental and phylogenetic data to explore the individual/combined impacts of these predictors on diel emission patterns. We further investigated these patterns by conducting high‐resolution emission measurements in a subset of genetically distant species with contrasting temporal dynamics. While diel shifts in magnitude and richness of emission were strongly affected by genetic relatedness, they also reflect the environmental conditions under which the species grow. Specifically, light/dark emission ratios were negatively affected by an increase in winter temperatures, known to impact both plant physiology and insect locomotion, and sandy soil fractions, previously shown to exert stress that tempers with diel metabolic rhythms. Additionally, the biosynthetic origins of the compounds were associated with their corresponding production patterns, possibly to maximize emission efficacy. Using a multidisciplinary chemical/ecological approach, we uncover and differentiate the main factors shaping floral scent diel fluctuations, highlighting their consequences under changing global climate. Abstract : We reveal that phylogeny and environmental conditions strongly affect diel scent emission patterns in desert Brassicaceae species. Light/dark emission ratios are negatively affected by an increase in winter temperatures, rooted in plant/insect physiology, and sandy soil%, previously shown to exert a stress tempering with diel metabolic rhythms.